A Comprehensive Survey on Blockchain-Based Secure Storage Schemes for Medical Information (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The exponential growth of digital healthcare data and the increasing need for secure, interoperable medical information systems have positioned blockchain technology as a promising solution for medical data storage and sharing. This survey provides a comprehensive analysis of blockchain-based secure storage schemes for medical information, examining 140+ research papers published between 2018-2025. We systematically categorize existing approaches into five primary themes: privacy-preserving storage mechanisms, access control frameworks, interoperability solutions, consensus and trust models, and smart contract implementations. Our analysis reveals that hybrid architectures combining on-chain metadata with off-chain encrypted storage (particularly using IPFS and cloud services) have emerged as the dominant paradigm. Key cryptographic techniques include attribute-based encryption (ABE), homomorphic encryption, and differential privacy for protecting sensitive medical data. We identify permissioned blockchain platforms, especially Hyperledger Fabric and Ethereum-based private networks, as preferred choices for healthcare consortiums. Major challenges include scalability limitations, regulatory compliance (HIPAA, GDPR), interoperability with legacy systems, and governance frameworks. Recent advancements focus on post-quantum cryptography integration, AI-enabled healthcare blockchains, and patient-centric digital twin implementations. This survey concludes with a discussion of future research directions, including quantum-resistant security schemes, cross-chain interoperability, and standardization efforts for blockchain-based healthcare systems.